2014
DOI: 10.2478/acph-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the Essential Oil from Pimenta Pseudocaryophyllus as an Antimicrobial Agent

Abstract: This study evaluated the effectiveness of the essential oil of Pimenta pseudocaryophyllus in inhibiting the growth of the main bacteria responsible for bad perspiration odor (Staphylococcus epidermidis, Proteus hauseri, Micrococcus yunnanensis and Corynebacterium xerosis). The chemical profile of the essential oil was evaluated by high-resolution gas chromatography (HR-GC) and four constituents were identified, eugenol being the major component (88.6 %). The antimicrobial activity was evaluated by means of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…In this study, the release of potassium ions and 260 nm-absorbing cell material was also increased in the presence of the essential oils. Similar structural alterations were evidenced using the essential oil of Pimenta pseudocaryophyllus (Gomes) Landrum against the main bacteria responsible for bad perspiration odor ( Staphylococcus epidermidis or Proteus hauseri ) and Cinnamomum longepaniculatum (Gamble) N. Chao ex H. W. Li leaf essential oil against Staphylococcus aureus , E. coli and Salmonella enteritidis [ 49 , 50 ]. The essential oil of Melaleuca alternifolia L. (tea tree) disrupted the permeability barrier of E. coli and S. aureus membranes leading to the loss of chemiosmotic control [ 51 ].…”
Section: Mechanisms Of Essential Oil Cytotoxicitymentioning
confidence: 74%
“…In this study, the release of potassium ions and 260 nm-absorbing cell material was also increased in the presence of the essential oils. Similar structural alterations were evidenced using the essential oil of Pimenta pseudocaryophyllus (Gomes) Landrum against the main bacteria responsible for bad perspiration odor ( Staphylococcus epidermidis or Proteus hauseri ) and Cinnamomum longepaniculatum (Gamble) N. Chao ex H. W. Li leaf essential oil against Staphylococcus aureus , E. coli and Salmonella enteritidis [ 49 , 50 ]. The essential oil of Melaleuca alternifolia L. (tea tree) disrupted the permeability barrier of E. coli and S. aureus membranes leading to the loss of chemiosmotic control [ 51 ].…”
Section: Mechanisms Of Essential Oil Cytotoxicitymentioning
confidence: 74%
“…However, PEO contains eugenol as a major active component having strong inhibitory activity against both Gram-negative and Gram-positive bacteria ( Hyldgaard et al, 2012 ). The presence of eugenol might have resulted in morphological alterations of the microbial cell, including the disruption of the cell membrane, and formation cleft, and pore leading to the leakage of contents and subsequent death of microorganisms ( Suzuki et al, 2014 ). Moreover, eugenol can down-regulate several critical genes in S .…”
Section: Resultsmentioning
confidence: 99%
“…182.20) compound by the Food and Drug Administration ( FDA, 2016 ). The major component of PEO is eugenol (>80%) ( Suzuki et al, 2014 ). The PEO possesses antimicrobial activity against several microorganisms such as Staphylococcus epidermidis, Proteus hauseri, Micrococcus yunnanensis , and Corynebacterium xerosis ( Suzuki et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using crude extracts or essential oils obtained from P. pseudocaryophyllus leaves showed a wide potential of pharmacological properties, such as antimicrobial (Lima et al, ; Paula et al, ; Custódio et al, ; Fernandes et al, ; El Assal et al, ; Suzuki et al, ; Yokomizo and Nakaoka‐Sakita, ), anxiolytic, antidepressant (Fajemiroye et al, , ), antinociceptive, anti‐inflammatory (Paula et al, ), and antioxidant (Campanini et al, , ). Additionally, Ferrari et al () have recently shown the anti‐hyperuricemic effects of P. pseudocaryophyllus extracts from leaves and branches in hyperuricemic rats.…”
Section: Introductionmentioning
confidence: 99%